PENCAPAIAN STANDAR KOMPETENSI DALAM KURIKULUM 2006 PADA MATA PELAJARAN EKONOMI MELULUI PENDEKATAN KONTEKSTUAL (CONTEXTUAL TEACHING AND LEARNING) DI SMA NEGERI 11 SEMARANG - Hasyim, Moh. (Fakultas Ekonomi, Universitas Negeri Semarang, 2011)
The objective of this study is to know the effectiveness of contextual teaching and learning in economics subjet in SMA (senior high school) in achieving the standard of competency based on curriculum 2006. This research used quesi experiment research with randomized control group only. The result showed that contextual teaching and learning in Economics subject in SMA N 11 Semarang was very effectiveness in achieving the standard of competency based on curriculum 2006. The suggestions are: (1) it is needed a more comtrhensive study by using action research through cycling pattern so the percentage of Contextual Teaching and Learning (CTL) is found. (2) it is needed a preparation for teachers so they are ready to improve and innovate the way of teaching, (3) the implementation of CTL in groups can be tried in a bigger scope to support the implementation of KTSP (4) if three are students’ tasks of activities which do outside or at home, so teacher’s monitoring is needed, (5) it is needed to add individual tasks to decrease students’ dependence on their groups.